Implementing Enterprise VoIP Deployment - Basorun, Oluseyi; Mieee, Mnse Mnieee (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2016)
Voice over Internet Protocol (VoIP) is perceived as the best example of collaboration technology in today’s telecommunication space. There have being a paradigm shift from regular legacy telephone systems to VoIP over the last decade by most telecommunication and multinational companies globally. One of the huge benefit of VoIP is noticeable reduction in international call rates. In addition to the potential cost savings, VoIP offers the prospect of integrating voice with data and video applications, this goes a long way in increasing workers’ productivity within organizations. Many organizations are already embracing VoIP as replacement for their legacy PBX, others are integrating the existing PBX system with VoIP. This write up will focus on deployment of PBX-VoIP converged solution in enterprise organizations, where cost saving is one of the primary objectives.